China and IMO 2020 - Michal Meidan (The Oxford Institute for Energy Studies, 2019)
Shippers and refiners have been actively preparing for the IMO transition and engaged in a lively debate on how it would play out, and since the second half of 2019, making active preparations for it. Chinese refiners, however, seem to have been less preoccupied with it than their Western peers. This may seem surprising given that China holds the world's second largest refining capacity behind the US, is home to six of the 10 largest container ports globally, and is an early adopter of tighter shipping fuel emission standards domestically. One key reason is that China's domestic bunker market is small relative to its refining capacity and to other Asian hubs. At 20 Mt, it is about 2.5 time smaller than bunkering volumes at the port of Singapore alone (about 50 Mt). Of this 20 Mt, domestic bunkering account for 6-7Mt and bonded bunkering represents an additional 13 Mt. Yet the domestic tax system, which adds both consumer and value added taxes to bunker fuels, even for bonded sales, makes refinery based bunker fuels uncompetitive. It leaves blenders, who generally import about 90% of the material, mainly from Singapore and Malaysia, to dominate supplies. (...)
Keywords: 330; bunker fuels; China; Emissions; Gas; LNG; Oil; refining; Shipping